Single -and Multi-Walled Carbon Nanotubes as Nanocarriers for the Delivery of 7-Hydroxyflavone - Cecilia Espíndola; Alejandro Javier Correa; Manuel López-López; Pilar López-Cornejo; Eva Bernal; José Antonio Lebrón; Francisco José Ostos; Mohammed Rafii-; María Luisa Moyá (MDPI AG, 2022)
The research on flavonoids has exponentially grown since their first therapeutic evidence, in 1937. They are effective in vitro in a wide range of human diseases, particularly those mediated by free radicals, such as cancer, atherosclerosis, AIDS, or neuronal diseases. However, their applications have been reduced due to their low solubility, poor absorption, and rapid metabolism. Flavonoid encapsulation in nanocarriers significantly improves their oral absorption, protects the drug against degradation, decreases the first-pass hepatic effect, and makes absorption through the lymphatic system easier. In this work, carbon nanotubes were used as nanocarriers of 7-hydroxyflavone, 7-HF. The encapsulation of 7-HF into pristine single- and multi-walled carbon nanotubes, and into -COOH functionalized single-walled carbon nanotubes has been investigated. The equilibrium association constants were estimated. The structural backbone of 7-HF, two benzene rings linked through three carbon atoms that form a pyran heterocyclic ring containing a keto group, seems to play a key role in the 7-HF/CNT interactions, although other types of interactions are also at work. The in vitro release of 7-HF was studied at three pHs, 2.0, 7.4, and 9.2, mimicking the different biological barriers of the human organism.